PERAN GEN Z MENYONGSONG INDONESIA EMAS 2045: DETERMINASI MINAT PENGGUNAAN E-WALLET - Af'idah, Kamilatul; Sari, Dian Anita; Tasriastuti, Nurrohmi Ambar (STKIP Persada Khatulistiwa Sintang, 2025)
The research reason is due phenomenon of research results show the e-wallet transactions are in the public’s best preferred and the predictions that the growing value of the digital economy is key to achieving Indonesia Emas 2045. This research identifies the impacts of financial knowledge, ease of use perception and risk perception on attraction to using e-wallets among the students of Management Program at Universitas YPPI Rembang. The research data collection technique used a survey through questionnaires. The population research is active students of Universitas YPPI Rembang, Management Program year 2021 to 2023 total of 236. Proportional random sampling of 70 respondents was used for the inquiry. The data analysis applied multiple linear regression method. The findings reveal: 1) financial literacy and ease of use perception positive significantly attraction to using e-wallets, 2) risk perception negative and non-significant attraction to using e-wallets. Based on the determination test, regression model from financial literacy, ease of use perception and risk perception can influence the dependent variable of attraction in e-wallets by 66%. The closed-ended questionnaire restricts respondets assessments beyond the given statements, presenting a limitation thi this study.